2013
DOI: 10.1016/j.chembiol.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Biology Approach to Interrogate Quorum-Sensing Regulated Behaviors at the Molecular and Cellular Level

Abstract: SUMMARY Small molecule probes have been employed extensively to explore biological systems and elucidate cellular signaling pathways. In this study, we utilize an inhibitor of bacterial communication to monitor changes in the proteome of Salmonella enterica serovar Typhimurium with the aim of discovering new processes regulated by AI-2-based quorum sensing (QS), a mechanism of bacterial intracellular communication that allows for the coordination of gene expression in a cell density-dependent manner. In S. typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Among these, EOs are promising antimicrobial natural products. They are volatile natural mixtures of compounds consisting mainly of terpenoid and phenolic compounds, distilled from different parts of the plant and exhibiting both antimicrobial and anti-QS activities [14][15][16]. In our previous study, a thymol-carvacrol chemotype Lippia origanoides EO (LOT-II) was a potent QS inhibitor against C. violaceum [17].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, EOs are promising antimicrobial natural products. They are volatile natural mixtures of compounds consisting mainly of terpenoid and phenolic compounds, distilled from different parts of the plant and exhibiting both antimicrobial and anti-QS activities [14][15][16]. In our previous study, a thymol-carvacrol chemotype Lippia origanoides EO (LOT-II) was a potent QS inhibitor against C. violaceum [17].…”
Section: Introductionmentioning
confidence: 99%
“…These results open new avenues toward tracking and understanding the fate and function of the elusive quorumsensing signaling molecule.Over the past decade,o ur group and others have investigated the bacterial biochemical properties of (4S)-4,5dihydroxy-2,3-pentanedione (DPD). [1] Our interest in this molecule originally stemmed from its distinct densely oxygenated five-carbon-atom makeup,a nd reports touting its ability to coordinate gene expression in both gram-negative and gram-positive bacteria in ap opulation-dependent manner,t ermed as autoinducer-2 quorum sensing (AI-2 QS). Moreover,w eh ave shown that DPD can exist in ac omplex, multispecies equilibrium whereby its unique architecture allows it to undergo cyclization and ring-opening reactions in as imilar fashion as do saccharides (Scheme 1A).…”
mentioning
confidence: 99%